A case of long-term survival after surgical resection for solitary adrenal recurrence of esophageal squamous carcinoma - Kanaya, Nobuhiko (Surg Case Rep, 2017)
BACKGROUND: Esophageal carcinomas are highly malignant tumors with a high frequency of lymph node and distant organ metastasis. Treatment for recurrent tumors is generally decided on an individual basis. Although multidisciplinary treatments involving chemotherapy, surgical resection, and radiation are performed, the prognosis remains poor. Here, we report a case of prolonged recurrence-free survival (38 months) after esophageal carcinoma surgery and subsequent laparoscopic adrenalectomy for right adrenal metastasis. CASE PRESENTATION: An 83-year-old man was diagnosed with type 3 esophageal squamous cell carcinoma (T3N1M0, cStage IIIA, UICC-7), spreading from the lower thoracic esophagus to the abdominal esophagus. He underwent thoracoscopic esophagectomy with a two-field lymph node dissection followed by substernal gastric tube reconstruction. The final diagnosis was moderately differentiated squamous cell carcinoma (T3N2M0, fStage IIIB). Adjuvant chemotherapy was not administered because of the advanced age and postoperative condition of the patient. Computed tomography (CT) at 14 months postoperatively showed a mass with a 2-cm diameter at the right adrenal gland. Positron emission tomography (PET)/CT revealed a high fluorodeoxyglucose (FDG) uptake in the mass. It was suspected that the mass was a metastatic lesion secondary to the primary esophageal carcinoma. No metastases to lymph nodes or other distant organs were identified. The patient underwent laparoscopic right adrenalectomy. The histopathological examination revealed moderately differentiated squamous cell carcinoma, suggesting metastasis from the primary esophageal carcinoma. He has survived without recurrence for 38 months since laparoscopic adrenalectomy to remove the right adrenal metastastic mass after the esophageal carcinoma surgery. CONCLUSIONS: We describe a very elderly male who survived laparoadrenalectomy for right adrenal metastasis following esophageal cancer surgery without recurrence for 38 months postoperatively. Therefore, surgical resection might be an option for solitary adrenal recurrence.